2017
DOI: 10.1021/acs.macromol.7b02009
|View full text |Cite
|
Sign up to set email alerts
|

“Rubbery Stiffening” and Rupture Behavior of Freely Standing Nanometric Thin PIB Films

Abstract: Prior bubble inflation studies have shown strong evidence of rubbery-like stiffening behaviors for several organic and inorganic thin films. The possible origin is still unclear, but recently Ngai et al. [J. Polym. Sci., Part B: Polym. Phys.201351214224] and Li and McKenna [Macromolecules20154863296336] proposed that the separation of molecular motions and dynamic fragility are closely related to the observed rubber-like stiffening behavior. In the present work, we report observations from bubble inflation mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 94 publications
2
26
0
Order By: Relevance
“…4B) is lower than the reported macroscopic value (−6.33) ( 43 ). This behavior is similar to prior observations of rubber-like stiffening seen ( 42 ) in bubble inflation measurements on ultrathin films of several polymeric materials. McKenna and coworkers ( 41 , 42 ) observed that the compliance decreased as the film thickness decreased, and they interpreted this behavior as being due to the separation of α relaxation and Rouse mode caused by nanoconfinement effects.…”
Section: Introductionsupporting
confidence: 90%
See 4 more Smart Citations
“…4B) is lower than the reported macroscopic value (−6.33) ( 43 ). This behavior is similar to prior observations of rubber-like stiffening seen ( 42 ) in bubble inflation measurements on ultrathin films of several polymeric materials. McKenna and coworkers ( 41 , 42 ) observed that the compliance decreased as the film thickness decreased, and they interpreted this behavior as being due to the separation of α relaxation and Rouse mode caused by nanoconfinement effects.…”
Section: Introductionsupporting
confidence: 90%
“…Thus, it is a challenge to perform traditional dynamic measurements on these small amounts of material ( 4 ). To overcome this issue, in the present work, we have used the Texas Tech University (TTU) nanobubble inflation technique ( 41 , 42 ) to measure the viscoelastic response of the ultrastable Teflon films in the deep glassy regime in order to test the temperature dependence of the dynamics in the upper bound conditions, i.e., over a range that includes T f to T g . Prior bubble inflation studies have successfully shown that viscoelastic properties can be measured with sample sizes ranging from nano- to micrograms ( 41 , 42 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations